Análise experimental da mudança de fase de bioPCM em espuma metálica de geometria retangular e perfilada - Becker, Fábio (Universidade do Vale do Rio dos Sinos, 2025)
As a result of the gradual energy transition, with the increasing use of cleaner energy sources, energy storage becomes inevitable, mainly due to the seasonality of generation from such sources. In this context, one of the main existing alternatives is energy storage through latent heat. The main characteristic of this type of storage is its high energy storage density at a virtually constant temperature—that is, at the temperature at which the phase change occurs—which makes it possible to use it in numerous applications. Materials based on this form of storage are known as Phase Change Materials (PCMs). Due to their wide range of applications, the use of bio-based PCMs (bioPCMs) is important to mitigate potential environmental impacts. However, PCMs generally have low thermal conductivity, which may limit some applications. Therefore, methods that can improve heat transfer are necessary. The incorporation of metallic foams with different morphological characteristics into PCM is an efficient alternative that has been investigated due to its high heat exchange surface area and improved thermal conductivity. In this context, this research proposes a study with different foam geometries, along with the use of palm wax as bioPCM. Thus, two nickel foam geometries were used: one rectangular and the other profiled, which resembles a fin geometry. This allows for increased heat transfer and efficiency with a smaller foam volume. Furthermore, the influence of changing the reservoir orientation, analogous to the tilt of a photovoltaic module, was also analyzed. The main results showed that the case containing rectangular foam reduced the charging (fusion) time by 7.5% and the discharging (solidification) time by 4%, compared to the case without foam, while the case containing the profiled geometry reduced the charging time by 7.1% and increased the discharging time by 10%. The inclusion of foam also improved the energy storage rate by approximately 8.1% for the rectangular geometry and by 7.6% for the profiled geometry.
Keywords: Materiais de Mudança de Fase (PCM); Espuma metálica; Fusão; Solidificação; Phase Change Material (PCM); Metal foam; Melting; Solidification; ACCNPQ::Engenharias::Engenharia Mecânica